FAIR VALUE OF NON-CURRENT ASSETS AND THE SECOND LARGEST OWNERSHIP ON AUDIT FEE - Hapsari, Beriliana; Apandi, R. Nelly Nur (The International Journal of Business Review (The Jobs Review), 2018)
The use of fair value method has positive and negative impact. The positive impact of applying the fair value method is more relevant for the decision maker and shows the economic value according to the circumstances at that time. While its negative impact, can lead to manipulation and uncertainty. It takes greater effort for the auditor to assess fairness of fair non-current asset quality, resulting in increased audit fees. This study aims to determine the effect of fair value of non-current asset on the determination of audit fees and to know the multiple large shareholder moderation in the relationship between fair value of non-current asset and audit fee. Using the OLS regression, this study uses companies listed on the IDX from 2013 to 2015 with the exception of the financial sector. The result of this research indicates that fair value of non-current asset influences audit fee and this research shows that the second largest ownership can weaken the effect of fair value of non-current asset towardÂ  audit fees.